If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4k+3(k+2)=-8(k-3)+6k
We move all terms to the left:
4k+3(k+2)-(-8(k-3)+6k)=0
We multiply parentheses
4k+3k-(-8(k-3)+6k)+6=0
We calculate terms in parentheses: -(-8(k-3)+6k), so:We add all the numbers together, and all the variables
-8(k-3)+6k
We add all the numbers together, and all the variables
6k-8(k-3)
We multiply parentheses
6k-8k+24
We add all the numbers together, and all the variables
-2k+24
Back to the equation:
-(-2k+24)
7k-(-2k+24)+6=0
We get rid of parentheses
7k+2k-24+6=0
We add all the numbers together, and all the variables
9k-18=0
We move all terms containing k to the left, all other terms to the right
9k=18
k=18/9
k=2
| 2xx20=180 | | g-1=6.1 | | 8+-2x=2x+6 | | 5x+2(6x-4)=145 | | 50=p-10+11 | | 3n-3/2n+5=8/6 | | (3x+7)+(5x+-35)=360 | | 14+9r+20=16r−15 | | a+2=23 | | 7(x−4)=42 | | 3x-10+2x=4x+5+6x+10 | | -2(x-2)=24+3x | | 7-6x=7x-58 | | 20=1/2x+6 | | 6c-4-2=-27 | | 6-7a=13 | | -4+16h=18h | | 8+3n=n+6 | | 12^2+x^2=(x+4)^2 | | -3x(-4-2x)=-2(x-1) | | 9x+10-7x=5(x+3) | | (x+5)/6=2 | | 9m=67 | | q+-72=-27 | | 14x+5+21x=180 | | 2x1=x+13 | | -3x(-4-2x)=-2+x-1) | | 8÷x+8=5÷8 | | 64=-3(8+6r)-(r+7) | | 7r+2=3r-26 | | -6c+-4c=-6 | | 3x+15=5x-21 |